2020
DOI: 10.3390/ijms21155255
|View full text |Cite
|
Sign up to set email alerts
|

Distant Metastasis in Colorectal Cancer Patients—Do We Have New Predicting Clinicopathological and Molecular Biomarkers? A Comprehensive Review

Abstract: Colorectal cancer (CRC) remains a serious health problem worldwide. Approximately half of patients will develop distant metastasis after CRC resection, usually with very poor prognosis afterwards. Because patient performance after distant metastasis surgery remains very heterogeneous, ranging from death within 2 years to a long-term cure, there is a clinical need for a precise risk stratification of patients to aid pre- and post-operative decisions. Furthermore, around 20% of identified CRC cases are at IV sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 206 publications
1
44
0
Order By: Relevance
“…Even though initially carrying identical mutations, further mutations result in genetic heterogeneity between the primary tumor and metastases (intertumor heterogeneity). Thus, primary tumor and distant metastases must be considered genetically heterogeneous 15 …”
Section: Methodsmentioning
confidence: 99%
“…Even though initially carrying identical mutations, further mutations result in genetic heterogeneity between the primary tumor and metastases (intertumor heterogeneity). Thus, primary tumor and distant metastases must be considered genetically heterogeneous 15 …”
Section: Methodsmentioning
confidence: 99%
“… 26 , 27 The indications for liver metastasis site resection and interventional therapy need to be carefully evaluated in colon adenocarcinoma. 28 Recently, some reports suggested that liver metastasis site resection could also benefit co-NEC patients. 29 31 More attempts to improve co-NEC patient survival and quality of life were encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…During the slow development phases of polyp, different mutations start to accumulate and transform some of the polyps into malignant carcinoma [ 3 ]. Early stages of CRC are curable by surgery, however, when cancer metastasizes to lymph nodes or other distant organs, the prognosis of CRC becomes poor [ 4 ]. Furthermore, about 20% of CRC patients have already progressed into a metastatic state at the time of presentation and more than 30% of patients with early CRC have been reported to develop metastatic disease eventually [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%